Special features of radio pulse spectral density analysis - Chubykalo, Andrew; Espinoza, Augusto; Kuligin, Victor (CIENCIA ergo-sum; Vol. 27 Núm. 4 (2020): Número especial "Retos de la física no lineal"DO - 10.30878/ces.v27n4a2, 2020)
The spectrum analysis of the periodic sequence radio pulses is often described in textbooks. However, if this method is applied to short radio pulses with a large period between them, then large errors occur. In this article, we described a new method of pulse gating. This method allows us to measure the spectral density of radio signals with high duty cycle. The main advantages of our method are a high signal-to-noise ratio, a large dynamic range of measurements, and a higher accuracy of spectral density measurements.